Royal Sponsored Funeral Service after Establishing Service Sectors at the Provincial Level : A Case of Khon Kaen Province - Seehawi, Thanaphat (Journal of Graduate MCU KhonKaen Campus, 2022)
This research article aims to explain and reflect the response from service provision, problems, obstacles, as well as feedbacks for development and improvement of the royal sponsored funeral service. The data were purposively gathered from in-depth interviews with 2 groups of key informants who are related with funeral service: 1) the hosts or inheritors of the deceased who received the royal sponsored funeral service, and 2) the civil servants with working experience, not less than 1 year, in the position of team supervisor or team leader. The data from the interviews were analyzed by using thematic analysis approach and then each theme was connected and interpreted into the research framework. The results showed that the provincial royal sponsored funeral service serving in the area of Khon Kaen Province is responsive to needs of the relatives and families of the deceased after the establishment of a provincial service unit. It can be described according to the framework of people's satisfaction towards public services that include 5 dimensions: 1) equity2) timely service 3) adequate service 4) efficient service, and 5) proactive service. However, in providing services to the public, there are still some notable problems encountered during the operation such as unpredicted time and distance to the event, location, and different local traditions in each community. Therefore, the civil servants have to closely monitor all processes of the operation including evaluating the performance of the work to improve the quality of service. In addition, they provide convenience, speed, accuracy, and cost efficiency by employing the digital technology